Sosialisasi dan Pengembangan Situs Web di Madrasah Aliyah Ma’arif 1 Ponorogo - Asyhari, Moch Yusuf; Aria Bima, Alim Citra; Yunitasari, Yessi; Cahyono Putro, Moh. Rizal Bagus; Cahyo, Wahyu Nur (Fakultas Teknik dan Ilmu Komputer (FASTIKOM) UNSIQ, 2024)
Madrasah Aliyah Ma'arif 1 Ponorogo has introduced website development as a response to developments in information technology. This website is an important need in strengthening communication with students, parents and the community in today's digital era. The main problems faced are low access to school information and lack of interaction with the wider community. The solution to overcome this, website development facilitates easy access to information such as school profiles, academic programs, extracurricular activities, student achievements, as well as religious and social activities. The development method involves needs analysis, structured planning, comprehensive material collection, design and development, implementation, user training and outreach, and regular evaluation. The main goal is to strengthen the school's image at local and national levels, as well as increase community involvement in supporting modern and efficient education. This activity contributes to the development of information technology-based education, with a focus on increasing information accessibility and interaction of various lines in the context of Islamic education.